Alteramide B is a microtubule antagonist of inhibiting Candida albicans - Ding, Yanjiao; Li, Yaoyao; Li, Zhenyu; Zhang, Juanli; Lu, Chunhua; Wang, Haoxin; Shen, Yuemao; Du, Liangcheng (Biochimica et biophysica acta, 2016)
Alteramide B (ATB), isolated from Lysobacter enzymogenes C3, was a new polycyclic tetramate macrolactam (PTM). ATB exhibited potent inhibitory activity against several yeasts, particularly Candida albicans SC5314, but its antifungal mechanism is unknown. The structure of ATB was established by extensive spectroscopic analyses, including high-resolution mass spectrometry, 1D- and 2D-NMR, and CD spectra. Flow cytometry, fluorescence microscope, transmission electron microscope, molecular modeling, overexpression and site-directed mutation studies were employed to delineate the anti-Candida molecular mechanism of ATB. ATB induced apoptosis in C. albicans through inducing reactive oxygen species (ROS) production by disrupting microtubules. Molecular dynamics studies revealed the binding patterns of ATB to the β-tubulin subunit. Overexpression of the wild type and site-directed mutants of the β-tubulin gene (TUBB) changed the sensitivity of C. albicans to ATB, confirming the binding of ATB to β-tubulin, and indicating that the binding sites are L215, L217, L273, L274 and R282. In vivo, ATB significantly improved the survival of the candidiasis mice and reduced fungal burden. The molecular mechanism underlying the ATB-induced apoptosis in C. albicans is through inhibiting tubulin polymerization that leads to cell cycle arrest at the G2/M phase. The identification of ATB and the study of its activity provide novel mechanistic insights into the mode of action of PTMs against the human pathogen. This study shows that ATB is a new microtubule inhibitor and a promising anti-Candida lead compound. The results also support β-tubulin as a potential target for anti-Candida drug discovery. ATB, a new polycyclic tetramate macrolactam (PTM) compound, was isolated and shown to have potent activity against Candida albicans SC5314 in vitro and in vivo. ATB induced apoptosis of C. albicans through inducing the production of reactive oxygen species (ROS) by disrupting microtubules. [Display omitted] •ATB is a novel PTM compound.•ATB shows potent in vitro and in vivo anti-Candida activity.•ATB induces apoptosis in C. albicans through increasing the production of ROS.•ATB is a new microtubule inhibitor and a promising anti-Candida lead compound.